2012
DOI: 10.4049/jimmunol.1201269
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Apoptosis and Induction of Foxp3+ Regulatory T Cells Underlie the Therapeutic Efficacy of CD4 Blockade in Experimental Autoimmune Encephalomyelitis

Abstract: The pathogenesis of multiple sclerosis requires the participation of effector neuroantigen-specific T cells. Thus, T cell targeting has been proposed as a promising therapeutic strategy. However, the mechanism underlying effective disease prevention following T cell targeting remains incompletely known. We found, using several TCR-transgenic strains, that CD4 blockade is effective in preventing experimental autoimmune encephalopathy and in treating mice after the disease onset. The mechanism does not rely on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 69 publications
3
20
0
Order By: Relevance
“…It has been shown that immunosuppressive reagents can induce Treg cells independently of the addition of exogenous TGF-β to the cultures [31]. The therapeutic induction of Foxp3+ Treg cells can then protect from inflammatory pathology such as arthritis or neuro-inflammation [32,33]. …”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that immunosuppressive reagents can induce Treg cells independently of the addition of exogenous TGF-β to the cultures [31]. The therapeutic induction of Foxp3+ Treg cells can then protect from inflammatory pathology such as arthritis or neuro-inflammation [32,33]. …”
Section: Resultsmentioning
confidence: 99%
“…Targeting CD4 and CD8 with ND Abs has been shown to prevent T cell activation, suppress ongoing effector functions, and induce tolerance in a wide range of models of immune pathology (28,(30)(31)(32)(33). The current study demonstrates that YTS-induced islet purging is due to direct suppression of pathogenic T cells, which limits the local inflammatory and chemoattractive milieu needed for tissue retention.…”
Section: Discussionmentioning
confidence: 99%
“…(28,29). The use of nondepleting (ND) Abs specific for CD4 and CD8 has also been effective at inducing allograft-and tissue-specific tolerance in a variety of transplantation and autoimmune models, respectively (28,(30)(31)(32)(33). ND anti-CD4 Abs have been used in clinical studies, most recently in NCT0148-1493.…”
Section: Introductionmentioning
confidence: 99%
“…Immune tolerance can be achieved by timely administration of non‐depleting anti‐CD4, which in most cases leads to induction of CD4 + Foxp3 + T cells that are responsible for the tolerant state 11 , 12 , 17 , 18 , 19 . The antibody is said to be non‐depleting as its isotype does not lead to direct T‐cell lysis 6 , 24 . However, the dynamics of T cells under non‐depleting anti‐CD4 administration are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all the studies on tolerance induction using non‐depleting anti‐CD4 MAbs over the years, the role played by this molecule on T‐cell dynamics still remains to be elucidated. Although several studies have shown that Foxp3 induction is the main mechanism by which anti‐CD4 MAb lead to tolerance, 17 , 18 , 19 , 20 , 21 , 22 there are also some reports indicating that an additional role of CD4 blockade in tolerance induction is related to apoptosis of effector T cells, that is, activated antigen‐specific T cells 15 , 23 , 24 …”
mentioning
confidence: 99%